An updated systematic review and meta-analysis of fecal microbiota transplantation for the treatment of ulcerative colitis. Issue 30 (29th July 2022) - Huang, Taobi; Xu, Jinlan; Wang, Maoying; Pu, Ke; Li, Longquan; Zhang, Huiyun; Liang, Yuan; Sun, Weiming; Wang, Yuping
Abstract : Background: Fecal microbiota transplantation (FMT) as a promising therapy for ulcerative colitis (UC) remains controversial. We conducted a systematic review and meta-analysis to assess the efficiency and safety of FMT as a treatment for UC. Methods: The target studies were identified by searching PubMed, EMBASE, the Cochrane Library, Web of Science, and ClinicalTrials and by manual supplementary retrieval. We conducted a general review and quantitative synthesis of included studies. We used the RevMan and Stata programs in the meta-analysis. The outcomes were total remission, clinical remission, steroid-free remission, and serious adverse events. We also performed subgroup analyses based on different populations. Results: A total of 34 articles were included in the general review. Only 16 articles, including 4 randomized controlled trials, 2 controlled clinical trials, and 10 cohort studies, were selected for the meta-analysis. We found that donor FMT might be more effective than placebo for attaining total remission (risk ratio [RR]: 2.77, 95% confidence interval [CI]: 1.54–4.98; P = .0007), clinical remission (RR: 0.33, 95% CI: 0.24–0.41; P < .05), and steroid-free remission (RR: 3.63, 95% CI: 1.57–8.42; P = .003), but found no statistically significant difference in the incidence of serious adverse events (RR: 0.88, 95% CI: 0.34–2.31, P = .8). The subgroup analyses revealed significant differences between the pooled clinical remission rates for different regions, degrees of severity of the disease, and patients with steroid- or nonsteroid-dependent UC. Conclusions: FMT can achieve clinical remission and clinical response in patients with UC.